Hypercommodification in Indonesian Mass Media and its Impact on Society: A Study and Suggestions - Muzhaffar Shidqi, Raihan; KN, Jamiati (COMMUSTY Journal of Communication Studies and Society, 2022)
This research focuses on increasing the commodification of media products, the proliferation of consumerist values, and their impact on media content, ownership, and political discourse. The findings show that the hyper-commodification of society in Indonesia has led to significant changes in the mass media industry, focusing on profit-driven media products and decreasing independent and diverse media content. This research also highlights the need for media literacy and education initiatives to counteract the effects of consumerism and to promote critical and informed media consumption. Overall, this research sheds light on the complex and interrelated processes of commodification, consumerism and mass media, and their impact on Indonesian society and culture.